Mathematical Representation Ability of Students With Moderate Visual Spatial Intelligence in Solving Solid Figure Problems - Anugrah, Dian; Ma'rufi, Ma'rufi; Hidayat, Rahmat (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
The importance of the ability of representation as a standard process of learning mathematics because it can help students understand and develop every concept in learning mathematics. The representation of each element of intelligence which dominates a lot is visual-spatial intelligence because it is an object that can be seen visually. Winsgoal tidak hanya menyediakan kemudahan deposit qris, tetapi juga tersedia deposit idn slot pulsa tanpa potongan, e-wallet dan transfer bank yang tidak kalah menarik. However, it is known from previous researchers that the ability of students' mathematical representations is still relatively low. This is due to the habit of students receiving direct learning and passive activities. This research is a qualitative research that aims to describe the representation abilities of students with visual-spatial intelligence who are currently solving geometric problems. The subjects of this study were class XII MIPA students at SMAN 9 Enrekang. Data were collected using a visual-spatial intelligence test instrument, a mathematical representation ability test instrument and interviews on students' mathematical representation abilities. The data that has been obtained is analyzed using the Nvivo 12 Plus application. The results showed that students with visual-spatial intelligence were able to represent problems visually and verbally in solving spatial geometry problems but could not represent them mathematically. This is based on the fact that students are not precise in choosing the mathematical model used in solving geometrical problems so that students experience problems in solving the next problem. Choosing innovative learning methods and getting students used to working on questions that require higher-order thinking skills can support students' mathematical representation abilities.